Network of proteins, enzymes and genes linked to biomass degradation shared by Trichoderma species. Issue 1 (December 2018) - Horta, Maria; Filho, Jaire; Murad, Natália; Santos, Eidy; Santos, Clelton; Mendes, Juliano; Brandão, Marcelo; Azzoni, Sindelia; Souza, Anete
Abstract Understanding relationships between genes responsible for enzymatic hydrolysis of cellulose and synergistic reactions is fundamental for improving biomass biodegradation technologies. To reveal synergistic reactions, the transcriptome, exoproteome, and enzymatic activities of extracts fromTrichoderma harzianum, Trichoderma reesei andTrichoderma atroviride under biodegradation conditions were examined. This work revealed co-regulatory networks across carbohydrate-active enzyme (CAZy) genes and secreted proteins in extracts. A set of 80 proteins and respective genes that might correspond to a common system for biodegradation from the studied species were evaluated to elucidate new co-regulated genes. Differences such as one unique base pair between fungal genomes might influence enzyme-substrate binding sites and alter fungal gene expression responses, explaining the enzymatic activities specific to each species observed in the corresponding extracts. These differences are also responsible for the different architectures observed in the co-expression networks.